Conservation Agriculture and Climate Change - Hassan, Baidaa Alawi; Jaber, Baidaa Hamid (American Journal of Botany and Bioengineering, 2025)
Due to salinization, scarcity of fresh surface and groundwater resources, and climate changes that negatively affect the stability of agricultural production (both plant and animal), including declining rainfall rates and their poor distribution during the agricultural season, high temperatures, and desertification, the agricultural sector is one of the sectors most affected by climate change. It has become necessary for those interested in the agricultural sector, including researchers and farmers, to search for sustainable, productive, and profitable agricultural production methods that are less depleting of agricultural natural resources, such as soil and water. Applying climate-smart agricultural technologies that ensure increased agricultural production while maintaining the sustainability of agricultural natural resources is crucial. The basic solution is to apply the Conservation Agriculture (CA) system, which contributes to increasing the efficiency of using limited water resources and stopping the deterioration of agricultural lands, effectively achieving food security.